Consumer Mentality: Existential Considerations - Soghomonyan , Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
Civilization is gradually approaching a dangerous boundary, full of temptations, beyond which the influence of uncontrolled forces may prove fatal for humanity. The absence of cultural-anthropological rootedness in existence gives rise to a paradoxical socio-psychological sensation of a vanishing reality. In place of reality, a hyperreality or virtual reality takes shape, where it no longer matters what is real and what is not. Life unfolds as a transcendental movement of creating simulacrums and illusions that mask the absence of the original reality. Spiritual values gradually undergo transformation and become symbolic images of commodities. A new stratum of people with narrow and limited views and aspirations is being formed, for whom brand identity becomes the primary criterion of self-identification. Man relinquishes long-term goals, which, by simplifying existence, leads to an existential devaluation of life. The "deal" becomes more important than the existential price to be paid for it. In the context of current civilizational transformations, preserving existential integrity requires abandoning the obsession with absolute evolutionism and, by limiting being, making conscious efforts toward the co-development (coevolution) of the natural (the spiritual-bodily wholeness of the human being) and the artificial (virtual reality, artificial intelligence) - for the sake of preserving the wholeness of existential being.
Keywords: civilizational transformation; body; simulacrum; virtual reality; simulation; hyperreality; mass culture; existential integrity; existential price